Intramuscular myxoma of the deltoid muscle in a swimmer: A rare case report and literature review - Saulius Adamonis; Bassey Enodien; Stephanie Taha‐Mehlitz; Andreas Maurer; Anas Taha (Clinical Case Reports, 2019)
Abstract Intramuscular myxoma (IM) is a rare mesenchymal neoplasm with the incidence of one per 1 000 000 people and is reported greater among women. Our case reports an IM of a deltoid muscle in a young man. Differential diagnosis with sarcoma is important. Surgery is the treatment of choice usually without recurrence.